2014
DOI: 10.4161/tisb.28755
|View full text |Cite
|
Sign up to set email alerts
|

PLEKHA7 modulates epithelial tight junction barrier function

Abstract: PLEKHA7 is a recently identified protein of the epithelial zonula adhaerens (ZA), and is part of a protein complex that stabilizes the ZA, by linking it to microtubules. Since the ZA is important in the assembly and disassembly of tight junctions (TJ), we asked whether PLEKHA7 is involved in modulating epithelial TJ barrier function. We generated clonal MDCK cell lines in which one of four different constructs of PLEKHA7 was inducibly expressed. All constructs were localized at junctions, but constructs lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…6C). The TJ markers ZO-1 and cingulin were detected in PLEKHA7 IPs-not only in mCCD cells, supporting our previous observations in MDCK cells 85 -but also in meEC cells (Fig. 6A).…”
Section: Figure 5 Proximity Between Plekha7 and Cingulin In Endothelsupporting
confidence: 89%
“…6C). The TJ markers ZO-1 and cingulin were detected in PLEKHA7 IPs-not only in mCCD cells, supporting our previous observations in MDCK cells 85 -but also in meEC cells (Fig. 6A).…”
Section: Figure 5 Proximity Between Plekha7 and Cingulin In Endothelsupporting
confidence: 89%
“…Therefore, the growth-suppressing or growth-promoting functions of p120 and E-cadherin are fine-tuned by binding to PLEKHA7. Further interactions of PLEKHA7 with paracingulin 54 , afadin 55 , ZO-1 and cingulin 56 , may also play a role in PLEKHA7 function, although the interaction with p120 is essential for modulating cell behaviour by regulating miRNA processing.…”
Section: Discussionmentioning
confidence: 99%
“…This may in turn be subjected to regulatory control mechanisms, for example through associations with other proteins, which may also control stability. With this in mind, we examined the relationships between the expression and localization of PLEKHA7 with that of the zonular tight junction proteins ZO-1 and cingulin, and the adherens junction proteins E-cadherin and p120ctn, with which PLEKHA7 forms complexes [ 13 , 17 ]. We found that when PLEKHA7 was expressed, its subcellular localization was very similar to, although not precisely overlapping with, that of ZO-1 and cingulin, at apical zonulae .…”
Section: Discussionmentioning
confidence: 99%
“…PLEKHA7 interacts not only with p120ctn and paracingulin, but also with the adherens junction protein afadin [ 16 ] and the microtubule minus-end capping protein nezha [ 13 ]. In addition, it forms a complex with the TJ proteins cingulin and ZO-1 [ 17 ]. Importantly, unlike E-cadherin and associated catenins (p120ctn, α-catenin and β-catenin), but similarly to paracingulin and afadin, PLEKHA7 is not distributed along lateral contacts ( puncta adhaerentia ) of polarized epithelial cells, but exclusively at circumferential apical zonulae adhaerentes (ZA) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%